A Case Series of Tooth Autotransplantation in Three Children with Different Presenting Complaints. (2nd October 2020) - Taheny, Maria; O'Murchu, Nora; McLaughlin, Paul; Cross, David
Abstract : This case series presents three successful cases of autotransplantation in paediatric patients at Glasgow Dental Hospital with differing clinical presentations. It successfully demonstrates the versatility of the technique. CPD/Clinical Relevance: Autotransplantation of teeth is a viable treatment option for the replacement of teeth in children and can be an excellent method of maintaining space and bone for restoration with an implant in adulthood.